PENGUKURAN MINAT BACA MAHASISWA DENGAN METODE CLUSTERING DI PERPUSTAKAAN AKADEMI KEPERAWATAN RS.DUSTIRA CIMAHI MENGGUNAKAN DATA MINING - Eryan Ahmad Firdaus; Shanti Maulani; Asep Budi Dharmawan (FKOM UNIKU, 2021)
Based on the results of research to measure students' reading interest in Akper RS. Dustira Cimahi Library can be done by using clustering method. In this study using library data, namely Akper RS. Dustira Cimahi library database. taken from three main table sources such as visitorlog table, collection table and member table which will then be integrated and selected so that it can be put together into a data warehouse. In using data mining, checking the title of the book collection to find out the title of the book that is in great demand by students and students of what level borrows the most books and also the most books read in Akper RS. Dustira Cimahi library. From this information, it can be concluded that final-level students prefer to borrow and read books than students who are still in the early semester. The book with the title Introduction to Basic Human Needs is most in demand and widely borrowed and read while the title of the collection of books that are very little borrowed and read is a book with the title Learn Computer Science. By using the cluster method it can be known that the category of Nursing books is a book that is in great demand by students while Computer Science books belong to the category of book collections that are very little in demand by all nursing students. Keywords: Clustering Method, Data Mining, Collection Table, Member Table, Visitorlog Table.